Colchicine for the primary prevention of cardiovascular events - Martí-Carvajal, Arturo J; Gemmato-Valecillos, Mario A; Monge Martín, Diana; De Sanctis, Juan Bautista; Martí-Amarista, Cristina Elena; Hidalgo, Ricardo; Alegría-Barrero, Eduardo; Riera Lizardo, Ricardo J; Correa-Pérez, Andrea (The Cochrane database of systematic reviews, 2025)
BACKGROUND: Atherosclerotic cardiovascular diseases (ACVDs), a condition characterised by lipid accumulation in arterial walls, which is often exacerbated by chronic inflammation disorders, is the major cause of mortality and morbidity worldwide. Colchicine, with its first medicinal use in ancient Egypt, is an inexpensive drug with anti-inflammatory properties. However, its role in primary prevention of ACVDs in the general population remains unknown. OBJECTIVES: To assess the clinical benefits and harms of colchicine as primary prevention of cardiovascular outcomes in the general population. SEARCH METHODS: We searched the Cochrane Heart Specialised Register, the Cochrane Central Register of Controlled Trials (CENTRAL), Ovid MEDLINE (including In-Process & Other Non-Indexed Citations), Ovid Embase, Web of Science, and LILACS. We searched ClinicalTrials.gov and WHO ICTRP for ongoing and unpublished studies. We also scanned the reference lists of relevant included studies, reviews, meta-analyses, and health technology reports to identify additional studies. There were no limitations on language, date of publication, or study setting. The search results were updated on 31 May 2023. SELECTION CRITERIA: Randomised controlled trials (RCTs) in any setting, recruiting adults without pre-existing cardiovascular disease. We included trials that compared colchicine versus placebo, non-steroidal anti-inflammatory drugs, corticosteroids, immunomodulating drugs, or usual care. Our primary outcomes were all-cause mortality, non-fatal myocardial infarction, stroke, and adverse events. DATA COLLECTION AND ANALYSIS: Two or more review authors independently selected studies, extracted data, and performed risk of bias and GRADE assessments. MAIN RESULTS: We identified 15 RCTs (1721 participants randomised; 1412 participants analysed) with follow-up periods ranging from 4 to 728 weeks. The intervention was oral colchicine compared with placebo, immunomodulating drugs, or usual care or no treatment. Due to biases and imprecision, the evidence was very uncertain for all outcomes. All trials but one had a high risk of bias. Five out of seven meta-analyses included fewer than six trials (71.4%). The objectives of the review were to assess cardiovascular outcomes in the general population, but many of the included trials focused on liver disease. Colchicine compared to placebo Colchicine may reduce all-cause mortality compared to placebo in primary prevention, but the evidence is very uncertain (risk ratio (RR) 0.68, 95% confidence interval (CI) 0.51 to 0.91; 6 studies, 463 participants; very low-certainty evidence; number needed to treat for an additional beneficial outcome (NNTB) 11, 95% CI 6 to 67). Colchicine may result in little to no difference in non-fatal myocardial infarction, but the evidence is very uncertain (RR 0.87, 95% CI 0.41 to 1.82; 1 study, 100 participants; very low-certainty evidence). Colchicine may not reduce the incidence of stroke, but the evidence is very uncertain (RR 2.43, 95% CI 0.67 to 8.86; 1 study, 100 participants; very low-certainty evidence). Regarding adverse events, colchicine may increase the incidence of diarrhoea (RR 3.99, 95% CI 1.44 to 11.06; 8 studies, 605 participants; very low-certainty evidence; number needed to treat for an additional harmful outcome (NNTH) 10, 95% CI 6 to 17), and may have little to no effect on neurological outcomes such as seizure or mental confusion (RR 0.72, 95% CI 0.31 to 1.66; 2 studies, 155 participants; very low-certainty evidence), but the evidence is very uncertain. The effect of colchicine on cardiovascular mortality is also very uncertain (RR 1.27, 95% CI 0.03 to 62.43; 2 studies, 160 participants; very low-certainty evidence). Colchicine may not reduce post-cardiac procedure atrial fibrillation, but the evidence is very uncertain (RR 0.74, 95% CI 0.25 to 2.19; 1 study, 100 participants). We found no trials reporting on pericardial effusion, peripheral artery disease, heart failure, or unstable angina. Colchicine compared to methotrexate (immunomodulating drug) Colchicine may result in little to no difference in all-cause mortality compared to methotrexate, but the evidence is very uncertain (RR 0.42, 95% CI 0.12 to 1.51; 1 study, 85 participants; very low-certainty evidence). We found no trials reporting other cardiovascular outcomes or adverse events for this comparison. Colchicine compared to usual care or no treatment The evidence is very uncertain about the effect of colchicine compared with usual care on all-cause mortality in primary prevention (RR 1.07, 95% CI 0.90 to 1.27; 2 studies, 729 participants; very low-certainty evidence). Regarding adverse events, colchicine may increase the incidence of diarrhoea compared to usual care, but the evidence is very uncertain (RR 3.32, 95% CI 1.56 to 7.03; 2 studies, 729 participants; very low-certainty evidence; NNTH 18, 95% CI 12 to 42). No trials reported other cardiovascular outcomes for this comparison. AUTHORS' CONCLUSIONS: This Cochrane review evaluated the clinical benefits and harms of using colchicine for the primary prevention of cardiovascular events in the general population. Comparisons were made against placebo, immunomodulating medications, or usual care or no treatment. However, the certainty of the evidence for the predefined outcomes was very low, highlighting the pressing need for high-quality, rigorous studies to ascertain colchicine's clinical impact definitively. We identified numerous biases and inaccuracies in the included studies, limiting their generalisability and precluding a conclusive determination of colchicine's efficacy in preventing cardiovascular events. The existing evidence regarding colchicine's potential cardiovascular benefits or harms for primary prevention is inconclusive owing to the limitations inherent in the current studies. More robust clinical trials are needed to bridge this evidence gap effectively.
Keywords: primární prevence; ateroskleróza; placebo; randomizované kontrolované studie jako téma; zkreslení výsledků (epidemiologie); cévní mozková příhoda; Adult; Placebos; Stroke; příčina smrti; dospělí; infarkt myokardu; Primary Prevention; Anti-Inflammatory Agents, Non-Steroidal; antiflogistika nesteroidní; kardiovaskulární nemoci; lidé; Atherosclerosis; Humans; Bias; Randomized Controlled Trials as Topic; Colchicine; Myocardial Infarction; kolchicin; antiflogistika; Cardiovascular Diseases; Anti-Inflammatory Agents; Cause of Death